(untitled) (Boletin Médico de Postgrado, 2020)
In order to determine the usefulness of the Flint Index as a predictor of postoperative complications in colon trauma in patients admitted to the Servicio de Cirugía General of the Hospital Universitario Dr. Antonio María Pineda, we conducted a cross-sectional descriptive study with 77 patients with an average age of 28.2 ± 10.8 years and predominance of male sex (98.7%). The most frequent mechanism of trauma was by single shot firearm (67.5%); the most affected segment was sigmoid colon (32.4%) and transverse (31.1%); 74% of patients had only one lesion in colon and the most common associated lesions were localized in small intestine (59.7%), liver (19.4%) and kidney (12.9%). According to the severity of trauma, perforation was found in 54.5% of cases, moderate contamination (42.8%), presence of associated lesions (85.7%), discrete hemodynamic situation (59.7%) and delay in treatment of less than 6 hours (45.4%). According to the Flint index, 51.9% of patients had a severity grade III, 40.2% grade II and 7.7% grade I. The treatment was surgical in 88.3% of cases and the most used surgical technique was primary raffia (55.8%), followed by resection/anastomosis (27.9%) and resection/colostomy (25%). In conclusion, the Flint scale is a predictive tool for postoperative complications in patients with colonic trauma.